SEMEANDO A CIDADANIA: um estudo sobre a formação e a atuação de educadoras sociais em prol do letramento - Ramos, Tais Nascarella (2009)
This Master s thesis has as a target to unveil lay educators pedagogical practice who work in informal education as well as the educational practice that they develop in favor of literacy. Approaching the three themes that guide this study informal education, lay educators education and literacy we talk abo ut the results obtainedin informal educational sites, establishing a counterpoint : to which extent the informal can be considered an educational site beneath the school? An empirical research was accomplished in the Sementinha Project, in the city of Santo André-SP, through observation of the educational practice of seven educators, through interviews (with the ex-Secretary of Education who implemented the Project in the city; with the general coordinators of the Sementinha Project; with four of the seven educators) and also, a bibliographical study about the emergence of the project in the city of Curvelo-MG. The analysis show that the informal education, as well as the social educators actions, develop literacy practices which are able to help in the pedagogical education of these children, motivating the citizen action that they, since they are small might make effective in the communities they live in.(AU)